2022
DOI: 10.3389/fnut.2022.898417
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Enhancing Effects of Co-treatment With Kalopanax pictus Nakai Bark and Nelumbo nucifera Gaertner Leaf Extract in a Cyclophosphamide-Induced Immunosuppressed Rat Model

Abstract: ObjectiveImmune system disorders can result in various pathological conditions, such as infections and cancer. Identifying therapies that enhance the immune response might be crucial for immunocompromised individuals. Therefore, we assessed the immune-enhancing effect of co-treatment with Kalopanax pictus Nakai Bark and Nelumbo nucifera Gaertner leaf extract (KPNN) in a cyclophosphamide (Cy)-induced immunosuppressed rat model.Materials and MethodsFor in vitro studies, macrophages and splenocytes were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Inflammatory M1 macrophages are also found in chronically inflamed tissues and have been shown to activate other immune cells such as monocytes, neutrophils, and T cells (43). In previous studies, the contents of total leukocytes, lymphocytes, granulocytes, and mid-size cells (Mid) were significantly decreased in the Cy-treated group compared with those in the normal group (12,15,17,40). As in the previous study, our results showed that the decreased number of immune cells in Cy-induced immunosuppressed rats significantly increased the number of total leukocytes, lymphocytes, granulocytes, and Mid after administration of EA extract.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Inflammatory M1 macrophages are also found in chronically inflamed tissues and have been shown to activate other immune cells such as monocytes, neutrophils, and T cells (43). In previous studies, the contents of total leukocytes, lymphocytes, granulocytes, and mid-size cells (Mid) were significantly decreased in the Cy-treated group compared with those in the normal group (12,15,17,40). As in the previous study, our results showed that the decreased number of immune cells in Cy-induced immunosuppressed rats significantly increased the number of total leukocytes, lymphocytes, granulocytes, and Mid after administration of EA extract.…”
Section: Discussionmentioning
confidence: 98%
“…MAPK and NF-κB signaling play critical roles in the immune response (28)(29)(30)(31)(32). A previous study reported that several natural products could show immune enhancement by activating the phosphorylation of inducible Nitric Oxide Synthase (iNOS), cyclooxygenase-2 (COX-2), NF-κB, and MAPKs (JNK, ERK, and p38) in RAW-264.7 cells (17,(33)(34)(35). Our results showed that p-ERK and p-NF-κB protein levels in the EA-treated group were higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations